Inside 3D printers - LaPierre, Yvette, 1963- (Core Library, an imprint of Abdo Pub., 2019)
"Introduces readers to the uses of 3D printers, the hardware and software that make 3D printers possible, and the future of 3D printing technology"--Provided by publisher.